N6-Methyladenosine-Related Long Non-Coding RNAs Are Identified as a Potential Prognostic Biomarker for Lung Squamous Cell Carcinoma and Validated by Real-Time PCR - Zhang, Wei; Zhang, Qian; Xie, Zhefan; Che, Li; Xia, Tingting; Cai, Xingdong; Liu, Shengming (Frontiers in Genetics, 2022)
Currently, the precise mechanism by which N6-methyladenosine (m6A) modification of long non-coding RNAs (lncRNAs) promotes the occurrence and development of lung squamous cell carcinoma (LUSC) and influences tumor microenvironment (TME) remains unclear. Therefore, we studied the prognostic value of m6A-related lncRNAs and their relationship with TME in 495 LUSC samples from The Cancer Genome Atlas (TCGA) database. Pearson’s correlation and univariate Cox regression analysis identified 6 m6A-related lncRNAs with prognostic values for LUSC patients. LUSC patients were divided into two subgroups (clusters 1 and 2) using principal component analysis. The expression of PD-L1 was lower in tumor tissues and cluster 2 of LUSC patients. Cluster 2 of LUSC patients had a high immune score, stromal score, and unique immune cell infiltration. The focal adhesion kinase (FAK) pathway and cytokine receptor pathways are enriched in cluster 1. The m6A-related lncRNA prognostic markers (m6A-LPMs) were established using the least absolute shrinkage and selection operator (LASSO) Cox regression analysis. The risk score was calculated by 4 m6A-LPMs and associated with OS, TME, clinicopathological characteristics of LUSC patients. After adjusting for age, gender, and stage, the risk score was also an independent prognostic factor for LUSC patients. Real-time PCR results showed that the expression of 4 m6A-LPMs was consistent with our prediction results. Our study found that 4 m6A-LPMs (AC138035.1, AC243919.2, HORMAD2-AS1, and AL122125.1) are closely associated with LUSC prognosis, in future, they may as novel diagnostic biomarkers for LUSC and provide new immunotherapy targets for LUSC patients.